Modelling trust dimensions on social media - Mičík, Michal; Gangur, Mikuláš; Eger, Ludvík (Journal of Business Economics and Management, 2022)
Trust plays an important role in social media communication. For companies, trust is an important determinant of successful online communication. Thus, there is a pressing need to understand consumers’ trust in the socially mediated environment This paper presents a research study focused on modelling trust dimensions on social media. The main objective of this research is to identify which dimensions of trust play the most significant role in building trust in communication on social media. The second objective is focused on the development and validation of the five-factor trust measurement scale. A questionnaire survey (n=1000) was used as a tool to gather data. Exploratory factor analysis, confirmatory factor analysis and multiple regression analysis were used for data analysis and modelling. The research findings provide a deeper understanding of the factors that influence trust in the context of social media communication and expand existing knowledge. The conducted research uncovers the main trust dimensions that can be used to influence consumers’ attitudes toward companies operating online. Our model can help companies shape their communication to the right tone by highlighting the crucial factors that have a direct influence on trust.